p54-Fc-Labeled Gold Nanoparticle-Based Lateral Flow Strip-Assisted Portable Devices for Rapid and Quantitative Point-of-Care Detection of ASFV Antibodies - Yang Yang; Yuhao Li; Ziyang Wang; Minglong Tong; Pengcheng Zhu; Juanxian Deng; Zongjie Li; Ke Liu; Beibei Li; Donghua Shao; Zhongren Zhou; Yafeng Qiu; et al. (Biosensors)
In this study, a novel rapid immunochromatographic (IC) test for African swine fever virus (ASFV) antibodies is presented. An immunochromatographic test (IC) is a detection technique that combines membrane chromatography with immunolabeling. This approach saves time for antibody preparation, resulting in a shorter production cycle. p54 is an important structural protein of African swine fever, and an ideal protein for serotype diagnosis. Gold nanoparticles are attached to the ASFV p54-Fc fusion protein, and the ASFV-specific antigen p54 and Staphylococcus aureus protein A (SPA) are labeled on a nitrocellulose membrane, at positions T and C, respectively. We developed a SPA double sandwich IC test strip, and assessed its feasibility using ASFV p54 and p54-Fc fusion proteins as antigens. ASFV p54 and p54-Fc fusion proteins were expressed and purified. A sandwich cross-flow detection method for p54, which is the primary structural protein of ASFV, was established, using colloidal gold conjugation. Our method can detect ASFV antibodies in field serum samples in about 15 min using a portable colloidal gold detector, demonstrating high specificity and sensitivity (1:320), and the coincidence rate was 98% using a commercial ELISA kit. The dilution of the serum sample can be determined by substituting the absorbance (T-line) interpreted by portable devices into the calibration curve function formula of an African swine fever virus standard serum. In summary, our method is rapid, cost-effective, precise, and highly selective. Additionally, it introduces a new approach for constructing IC test strips using SPA protein without antibody preparation, making it a reliable on-site antibody test for ASFV.